(untitled) (Journal of Hama University, 2022)
The research aimed to identifying the relationship between the use of distribution strategies and enhance of market share in Study in the Syrian trading corporation. By identifying the extent of the impact of each dimensions of distribution strategies, by determining the extent to which both the distribution strategies dimensions and the basic requirements of the application of distribution strategies role market share, the researchers relied on the prescriptive approach and the descriptive approach as a general approach to research, the questionnaire was distributed to 280 person from different levels in the Syrian trading corporation, and this study concluded several results, the most important of which was a moral relationship between the use of distribution strategies and the market share, and this relationship is acceptable and positive, and is due to the lack of human resource skills and an inappropriate distribution programme, the researchers have reviewed many important results and made several suggestions and recommendations, the most important of which was the need to develop an appropriate strategy for the use of distribution strategies supporting its operations within the overall strategy of the Enterprises and following up on its implementation and evaluation in order to achieve the basic objectives of the Enterprises.